The Effects of Dancing to Electronic Music and the Additional Intake of Psychoactive Drugs on the Experience of Trance - Thomas Schäfer; Patricia Kreuzburg (European Journal of Psychology Open, 2022)
Abstract: Background: Dancing to music can induce states of trance as well as very pleasant or ecstatic experiences – particularly when the music is repetitive, monotonous, and rhythmic. The consciousness-changing and trance-inducing effects of electronic music resemble some of the psychoactive effects induced by specific drugs. We hypothesized that the effects of dancing to electronic music alone and dancing combined with the intake of psychoactive drugs would produce similar levels of ecstatic trance. Methods: We investigated this hypothesis with 91 participants in a live club setting. About half of the participants had taken psychoactive drugs. We used the Phenomenology of Consciousness Inventory (PCI) to measure ecstatic trance. Results: As hypothesized, the trance depth was similar in participants who had taken drugs and those who had not. Equivalence testing showed no difference between the two groups. Discussion: The results show that, while dancing to electronic music, the intake of psychoactive drugs is not necessary to experience an ecstatic trance. This is relevant not only for understanding the effects of music and dance in everyday life but also for counseling and (music) therapy.